Design of a wideband inductively coupled loop feed patch antenna for UHF RFID tag - Bashri, M. S. R.; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (Czech Technical University, 2015)
A planar wideband patch antenna for ultra-high frequency (UHF) radio frequ ency identification (RFID) tag for metallic applications is presented in this research work. Three different shape patches ar e inductively coupled to a triangle loop to form wi de impedance bandwidth for uni- versal application UHF (860 – 960 MHz) RFID. The struc- ture of the proposed antenna exhibits planar profile to provide ease of fabrication for cost reduction well suited for mass production. The simulation of the antenna was carried out using Finite Elemen t Method (FEM) based software, Ansoft HFSS v13. The simulated and measured impedance bandwidth of 113 MHz and 117 MHz (Return Loss ≥ 6 dB) were achieved to cover the entire UHF RFID operating frequency band worldwide. The simulated and measured radiation patterns at the operating frequency of 915 MHz are in good agreement. Moreover the simulated maximum antenna gain at th e bore sight direction in free space and when mounted on 200 × 200 mm 2 metal plate are -5.5 dBi and -9 dBi res pectively which is enough to provide reasonable read range over the entire UHF RFID system operating band.